Contribuição ao estudo do controle de temperatura em componentes eletrônicos - Araújo Filho, Newton Félix de (1996)
A numerical model was developed to simulate the behavior of an electronic device. This device is characterized by a simplified geometric configuration with parallel plates of eletronic circuits, where an internai heat generation occurs. The plates an separatedl by a dielectric material, and cooled by convection. The model was developed using the finite control volume technique in order to solve the energy equation, in unsteady state and bidimensional regime. The equation take into account a non uniform heat generation on the domain and different regimes of operation. In the model, a numerical analysis was done in order to verify the influence of geometrical and design parameters of the electronic components and also thermal parameters of the cooling fluid in the temperature control of critics regions on such devices.